Análise dos royalties do petróleo sob a perspectiva jurídica - Santos, Taíla Bueno dos [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This research aims to discuss the division of royalties from a legal perspective and its substitute role towards the non-taxation at source, in other words the taxation of destiny at the Brazilian petroleum industry. The analysis aims to deal with the historical evolution in relation to the aspect of royalties’ payment and its deviation of compensatory character in order to supply the ICMS function. There are some specific study objects in this research: 1. how the transformation of royalties’ payment led to financial compensation; 2. to whom the transference of mineral rent belongs – to the UNIÃO or to the fortunate regions which the oil is extracted; 3. would a tax reform be enough to minimize the competition of States and Cities towards the royalties? The research aims to clarify the real expectation that States have on the royalties’ payment. There is no compensation for damage to the environment as it is stated by the initial characteristic of the Constitution, and, by the contrast, from a compensatory character, there is a lacking of taxation from the sector mentioned before, this fact damages the producing states checked out by this research

O presente trabalho visa discutir a divisão dos royalties sob a ótica jurídica e seu papel substituto referente a não tributação na origem, isto é, a tributação no destino no setor petrolífero brasileiro. A análise visa tratar da evolução histórica no que se refere ao aspecto do pagamento de royalties e seu desvio de caráter compensatório para suprir a função do ICMS. Entretanto, há três pontos de interesse específico 1) o que levou a transformação do pagamento dos royalties em compensações financeiras, 2) a quem pertence o repasse da renda mineral, se à União ou às regiões afortunadas por possuírem petróleo e, 3) se uma reforma tributária minimizaria a disputa dos Estados e Municípios pelos royalties. A pesquisa objetiva, esclarecer a real expectativa que os Estados têm sobre o pagamento dos royalties. Não há compensação por danos ao meio ambiente como a característica inicial elaborada pela Constituição, mas de caráter compensatório a ausência de tributação do setor em questão que prejudica os estados produtores e confrontantes
Keywords: Economia; Petróleo; Petroleo - Arrendamento